Distinct microRNA profiles are associated with the severity of hepatitis C virus recurrence and acute cellular rejection after liver transplantation. Issue 4 (22nd March 2013) - Joshi, Deepak; Salehi, Siamak; Brereton, Helen; Arno, Matthew; Quaglia, Alberto; Heaton, Nigel; O'Grady, John; Agarwal, Kosh; Aluvihare, Varuna
<x xml:space="preserve">Abstract</x> Recurrent hepatitis C virus (HCV) infection is associated with accelerated fibrosis rates after liver transplantation (LT) and is the leading cause of graft failure. Furthermore, distinguishing recurrent HCV from acute cellular rejection (ACR) can be problematic, and this can lead to inappropriate treatments and adverse outcomes. We hypothesized that intragraft microRNA (miRNA) expression profiles could distinguish the severity of recurrent HCV and differentiate recurrent HCV from ACR. We established meticulously matched post‐LT patient cohorts in order to derive robust global miRNA expression profiles and minimize the impact of variables known to influence HCV recurrence. These cohorts consisted of patients with slow HCV fibrosis progression (Ishak stage < F2), fast HCV fibrosis progression (Ishak stage ≥ F2), ACR, and nonviral etiologies. We found increased intragraft expression of miRNA‐146a, miRNA‐19a, miRNA‐20a, and miRNA‐let7e in slow progressors versus fast progressors, and we validated these findings with quantitative PCR. This miRNA network regulates the expression of cardinal genes implicated in promoting antifibrogenic, antiangiogenic, and anti‐inflammatory pathways. miRNA‐19a and miRNA‐20a were also specifically detected in the serum of slow progressors. Furthermore, intragraft miRNA expression distinguished fast HCV progression from ACR. Here, changes in the expression of key miRNAs regulating fibrogenic and angiogenic pathways were associated with fast HCV progression. We demonstrate specific miRNA expression signatures that discriminate the rates of fibrosis progression in patients with recurrent HCV, and we distinguish recurrent HCV from ACR after LT. A pathway analysis indicates that specific miRNAs may play a regulatory role in these processes. Selected miRNAs may serve as intragraft and serum biomarkers for recurrent HCV after LT and help to distinguish between ACR and recurrent HCV. Liver Transpl 19:383–394, 2013. © 2013 AASLD.